2010
DOI: 10.3892/mmr_00000323
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-inducing activity of compounds screened and characterized from cinobufacini by bioassay-guided isolation

Abstract: Abstract. cinobufacini (huachansu), an aqueous extract from the skin of the toad Bufo bufo gargarizans cantor, is a traditional chinese medicinal preparation widely used in clinical cancer therapy in China. Here, we screened and identified active compounds of cinobufacini and investigated their apoptosisinducing effect on HepG 2 cells. Screening was performed using bioassay-guided isolation. The effects of different fractions on the proliferation of HepG 2 cells were detected by the MTT assay. The extraction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
4
14
0
Order By: Relevance
“…However, little is known about its killing effect on osteosarcoma. Experimental pharmacodynamics and clinical study both indicate that cinobufacini has obvious killing effect on many kinds of tumor cells, and the mechanism may be related with the apoptosis-inducing effect on tumor cells (Qi et al, 2008;Qi et al, 2010b;Wang et al, 2010). Our research found that cinobufacini may inhibit the proliferation of OS-732 cells in a dose-dependent manner which was consistent with the above research results.…”
Section: Discussionsupporting
confidence: 81%
“…However, little is known about its killing effect on osteosarcoma. Experimental pharmacodynamics and clinical study both indicate that cinobufacini has obvious killing effect on many kinds of tumor cells, and the mechanism may be related with the apoptosis-inducing effect on tumor cells (Qi et al, 2008;Qi et al, 2010b;Wang et al, 2010). Our research found that cinobufacini may inhibit the proliferation of OS-732 cells in a dose-dependent manner which was consistent with the above research results.…”
Section: Discussionsupporting
confidence: 81%
“…Some reports have suggested that apoptosis of cancer cell lines was induced by bufosteroids, unique steroid compounds contained in toad skin extract and toad venom, such as bufalin and cinobufagin (15)(16)(17)(18)(19). Decrease in MDA-MB-231 cell numbers observed in our experiments may in inhibiting metalloproteinase activity and result in suppressing cancer cell migration in the collagen gels.…”
Section: Resultssupporting
confidence: 47%
“…22 Resibufogenin shows strong cytotoxic activities against human cancer cells through induction of apoptosis or G 1 -phase arrest. 23,24 Moreover, the growth inhibition effect of RB against human cancer cells was comparable to or stronger than paclitaxel. 19 However, the effect and precise mechanism of RB on pancreatic cancer has not been elucidated.…”
mentioning
confidence: 94%
“…Resibufogenin is one of the major active components in Huachansu, and it is regarded as a representative compound for the quality control of Huachansu . Resibufogenin shows strong cytotoxic activities against human cancer cells through induction of apoptosis or G 1 ‐phase arrest . Moreover, the growth inhibition effect of RB against human cancer cells was comparable to or stronger than paclitaxel .…”
Section: Introductionmentioning
confidence: 99%